2010
DOI: 10.1017/s0022109010000487
|View full text |Cite
|
Sign up to set email alerts
|

What Drove the Increase in Idiosyncratic Volatility during the Internet Boom?

Abstract: Aggregate idiosyncratic volatility spiked nearly fivefold during the Internet boom of the late 1990s, dwarfing in magnitude a moderately increasing trend. While some researchers argue that this rise in idiosyncratic risk was the result of changes in the characteristics of public firms, others argue that it was driven by the changing sentiment of irrational traders. We present evidence that the marketwide decline in maturity of the typical public firm can explain most of the increase in firm-specific risk durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(57 citation statements)
references
References 26 publications
5
51
1
Order By: Relevance
“…The size explanation for idiosyncratic risk is also supported by others; Bennett and Sias (2006) find that changes in the weights of small stocks and risky industries that make up a market portfolio are responsible for changes in firm-specific risk. Fink et al (2010) find that the increase in the percentage of young firms in the stock market can explain idiosyncratic risk. In addition, Vozlyublennaia (2011) reports that a stock's idiosyncratic risk is negatively related to a company's performance, size, and earnings.…”
Section: Literature On the Forces Driving Idiosyncratic Riskmentioning
confidence: 85%
See 2 more Smart Citations
“…The size explanation for idiosyncratic risk is also supported by others; Bennett and Sias (2006) find that changes in the weights of small stocks and risky industries that make up a market portfolio are responsible for changes in firm-specific risk. Fink et al (2010) find that the increase in the percentage of young firms in the stock market can explain idiosyncratic risk. In addition, Vozlyublennaia (2011) reports that a stock's idiosyncratic risk is negatively related to a company's performance, size, and earnings.…”
Section: Literature On the Forces Driving Idiosyncratic Riskmentioning
confidence: 85%
“…As Campbell et al (2001) have shown, unexplained volatility has increased over time, but it was found that after 2000, the upward trend reversed (Bennett and Sias 2006;Brandt et al 2010), and idiosyncratic risk has no long-term trend (Vozlyublennaia 2011). The literature has identified a number of explanations for the behavior of idiosyncratic risk: idiosyncratic volatility might capture the effect of a risk factor that is missing in Fama and French's (1993) three-factor model (Chen and Petkova 2012); or it might be determined by institutional ownership and earnings growth (Vozlyublennaia 2011;Xu and Malkiel 2003), company performance (Vozlyublennaia 2011), the age of firms (Bali et al 2008;Fink et al 2010), low-priced stocks (Bali et al 2008;Brandt et al 2010), retail trading and its relation to low-priced stocks (Brandt et al 2010), cash flow volatility (Irvine and Pontiff 2009), growth options (Cao et al 2008), or information quality Rajgopal and Venkatachalam 2011). Xu and Malkiel (2003) find that institutional ownership and expected growth in earnings could explain cross-sectional idiosyncratic risk and have a positive relationship.…”
Section: Literature On the Forces Driving Idiosyncratic Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability in the overall model and in coefficient significance when using the bias-adjusted forecasts suggests that the market adjusts to the bias in earnings forecasts. Several IV studies argue that newly listed firms may be responsible for the increase in IVs (Fama & French, 2004;Fink et al, 2010;Irvine & Pontiff, 2009;Wei & Zhang, 2006). If such is the case, we expect that the different volatility measures would be less volatile after controlling for newly-listed firms.…”
Section: Tablementioning
confidence: 85%
“…They state that prior studies use firm age as a life cycle proxy showing that idiosyncratic volatility is lower for older firms like the works of (Fink et al, 2010;Gaspar & Massa, 2006). On the opposite side, other studies find a positive relation between age and idiosyncratic volatility (Luo & Bhattacharya, 2009;Ferreira & Laux, 2007), whereas others like (Tan & Liu, 2016) finds no association between them.…”
Section: Literature Reviewmentioning
confidence: 96%